2014
DOI: 10.1007/s00586-014-3676-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survivors after surgical management of metastatic spinal cord compression

Abstract: Long-term metastatic cancer survivor patients are an increasing population with specific characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
3
9
0
4
Order By: Relevance
“…From these findings, it is obvious that besides overall survival in the whole cohort, preoperative KPS affects the survival of patients with single or multiple metastases. This is in line with previous studies that have identified performance status as one of the strongest prognostic factors for survival. In our study, KPS scores ranging from 80 to 100 were associated with a better prognosis compared to scores ranging from 10 to 40 (HR 4.95, 95% CI 2.66–9.22, P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…From these findings, it is obvious that besides overall survival in the whole cohort, preoperative KPS affects the survival of patients with single or multiple metastases. This is in line with previous studies that have identified performance status as one of the strongest prognostic factors for survival. In our study, KPS scores ranging from 80 to 100 were associated with a better prognosis compared to scores ranging from 10 to 40 (HR 4.95, 95% CI 2.66–9.22, P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Tabouret et al . found that a delay between the first symptom and surgery showed a tendency toward bad prognostic influence but failed to reach statistical significance. Park reported that median survival for patients who developed neurologic deficit in less than 72 h was 2.28 times longer compared to patients who developed it ≥72 h (8.7 vs 3.1 months); the difference was statistically significant between groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It would likely be useful to analyze prognosis for individual tumor types rather than grouping all tumor types together. However, Abouret et al reported similar results in that they found that visceral metastases were not significantly predictive of long‐term survival for various primary tumors. Third, in the present study we did not investigate the effect of chemotherapy because previous chemotherapy regimens varied between patients; those variations may have influenced survival.…”
Section: Discussionmentioning
confidence: 90%
“…found that primary tumor and visceral metastases were the only significant parameters, according to multivariate analysis, in which all the seven parameters were assessed: general condition, extent of extraspinal bone metastases, extent of spinal metastases, visceral metastases, primary tumor, severity of spinal cord palsy, and pathological fracture. Tabouret et al . reported that multiple systemic metastases were not significantly predictive of survival, although a comparative analysis among the long‐term survivors and the other patients with overall survival <2 years exhibited significant differences.…”
Section: Discussionmentioning
confidence: 96%